An Overview of the Potential Therapeutic Applications of CO-Releasing Molecules - Aiten Ismailova; David Kuter; D. Scott Bohle; Ian S. Butler (Bioinorganic Chemistry and Applications)
Carbon monoxide (CO) has long been known as the “silent killer” owing to its ability to form carboxyhemoglobin—the main cause of CO poisoning in humans. Its role as an endogenous neurotransmitter, however, was suggested in the early 1990s. Since then, the biological activity of CO has been widely examined via both the direct administration of CO and in the form of so-called “carbon monoxide releasing molecules (CORMs).” This overview will explore the general physiological effects and potential therapeutic applications of CO when delivered in the form of CORMs.